Identifying Motives for Sport Participation from the Perspective of Self- Determination Theory: Gender Differences - Manal M. Bayyat (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims (1) to identify motives of sport participation from the perspective of self- determination theory, and (2) to investigate gender differences between female and male subjects. The population of this study was female and male students of the School of Physical Education at the University of Jordan (n= 88, 120, respectively). In accordance with the self-determination theory, an Arabic version of the Sport Motivation Scale was used to collect the required data. The scale measures the different forms of motivation towards sport participation. It consists of various subscales of intrinsic motivation (IM-to know, IM-to accomplish, IM-to experience), extrinsic motivation (identified regulation, introjected regulation, external regulation) and amotivation. Results of the study revealed the mean value of 63.86 for the intrinsic motivation (high level), 58.46 for the extrinsic motivation (average level) and 10.91 for the amotivation low level. No statistically significant differences were found between female and male subjects in motivation subscales except for the "to know" which was 0.032, and the "amotivation" which was 0.005. In general, female and male participants were equally motivated. Future studies leading to female sports empowerment are encouraged.